Natural Law and the Law of Moses in Jewish Averroistic Philosophy. - Sadik, Shalom (Journal of Religion, 2022)
In order to understand the relationship between philosophy and religion, one of the major questions that must be explored is the relation between natural law and prophetic law. One of the main problems with modern research on this topic in the field of Jewish studies is that debate is relegated to the interpretation of only a few thinkers whose ideas are presumed to represent Judaism. The aim of this article is to begin remedying this issue by analyzing the relation between the Law of Moses and natural law as presented by four Jewish Averroists: Rabbis Isaac Albalag, Isaac Pulgar, Josef Ibn Kaspi, and Levi ben Abraham.